GENDER DISCRIMINATION IN THE WORKPLACE AND ITS IMPLICATIONS FOR REPRODUCTIVE HEALTH: SYSTEMATIC REVIEW - Dilma'aarij Agustia; Tantri Yunita Ratna; Alfira Fitriana; Pamogsa Daniyar; Bilqis Nur Mustofa; Debby Pratiwi; Dewi Faradillah (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2026)
Gender discrimination in the workplace remains a global issue affecting social, economic, and health aspects. Unequal treatment in wages, career advancement, promotion opportunities, and access to workplace resources may contribute to psychological stress and adverse reproductive health consequences among women. These conditions can impact reproductive health, including difficulties related to pregnancy, making this issue important to analyze and address. This study aims to explore workplace gender discrimination and its implications for reproductive health through a systematic review. The keywords used were “Gender Discrimination” AND “Work Environment” AND “Reproductive Health”. This study took articles from 2014-2024 that discussed gender discrimination in the workplace and its implications for reproductive health. Result is A total of 1,710 articles were obtained. In the analysis phase, seven articles were selected for analysis. The findings consistently showed that workplace gender discrimination negatively affects women’s reproductive health through several pathways, including chronic psychological stress, reduced access to reproductive health support, delayed pregnancy planning, lower childbirth intentions, menstrual disorders, and increased risks associated with hazardous occupational exposures. The reviewed studies also highlighted persistent inequalities in wages, promotion opportunities, and workplace treatment across various employment sectors and countries. Workplace gender discrimination across sectors affects reproductive health through stress, hazardous conditions, and reduced opportunities for family planning and sexual health. Gender discrimination in the workplace also directly affects women’s reproductive health. Keywords: discrimination, work environment, reproductive health, gender.